An Evaluation of Donor Deferrals in A Blood Bank of a Tertiary Care Hospital: A 3Â½-Year Study - Pai, Shweta; Chabba, Shiv Kumar (Annals of Pathology and Laboratory Medicine, 2020)
Background: Blood transfusion is a crucial life-saving procedure that has become an integral component of modern medicine. It is therefore, imperative that the supply chain of blood to blood banks be optimized so as to meet the minimum demand of patients. This goal can be readily achieved by forming a safe reduction policy in the deferral rate of potential donors. The aim of this study was to explore the various causes for donor deferrals and to assess their frequency over the past 3Â½ years in a blood bank of a tertiary care hospital in Bangalore city. Methods: The data for the current retrospective study was collected over a period of 3 years 6 months from October 2015 to March 2019. Donors were asked to fill in a questionnaire followed by physical examination and blood screening tests. Results: Out of 2942 potential blood donors, only 2781 were accepted while the remaining 161 were deferred, the deferral rate being 5.5%. The age group of the deferred donors ranged from 18 to 49 years old, the highest being between 21-30 years old. There was a total of 119 temporary deferrals and 42 permanent deferrals. The most common cause for temporary and permanent deferral was found to be hypertension and sero-positivity for HBV antigen, respectively. Conclusion: In descending order of frequency, the most common causes for permanent deferrals were transfusion transmitted infection, hepatitis-B, Hepatitis-C and HIV and that for temporary deferrals were hypertension, alcohol consumption and anaemia. By identification of the causes for temporary deferrals, appropriate measures can be put in place to motivate these potential donors to return for blood donation at a later date after the underlying cause has been rectified.